VO #022 Extra rate of UPVC pipe changed from PVC pipe for conduit works of BRAC University new campus project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding VO #022 extra rate of UPVC pipe changed from PVC pipe for conduit works of BRAC University new campus project.